Challinor, Stacey. The Legend of Peggy's Hollow, Cape Broyle. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a local legend from Cape Broyle, Newfoundland, told by Stacey Challinor, a Grade 7 student at Baltimore School. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Stacey writes, "Peggy's Hollw is a folklore story passed down from generation to generation in Cape Broyle. Everyone from around Cape Broyle tells the story differently, depending on who told them, but shares the same idea. Peggy's Hollow is on the south side of Cape Broyle, which is often said to be haunted by Peggy. She supposedly roams the fishings stages and southside at night looking for her long-lost husband, in her wedding dress, screaming his name in desperation."